Accelerated Degradation of Microplastics at the Liquid Interface of Ice Crystals in Frozen Aqueous Solutions. Issue 31 (23rd June 2022) - Tian, Chen; Lv, Jiaxin; Zhang, Wenchao; Wang, Han; Chao, Jin; Chai, Liyuan; Lin, Zhang
Abstract: Microplastics (MPs) are one of the emerging contaminants in environmental media, and they have raised great concern because they are resistant to degradation and persist in ecosystems. Although numerous advanced technologies have been developed, suitable technologies are still lacking for degradation of widespread MPs in the natural environment. We have discovered that MPs can be degraded exceptionally rapidly in frozen environments. Taking polystyrene (PS) as an example, its degradation rate in ice (−20 °C) is surprisingly competitive to most artificial technologies. PS particles are trapped and squeezed to achieve excited state ( 3 PS*) in the narrow space of the liquid layer between ice crystals, which further react with the highly concentrated dioxygen to selectively produce singlet oxygen ( 1 O2 ). The 1 O2 boosts PS oxidation in the liquid layer thus further causing accelerated degradation at freezing temperature. This finding offers a highly efficient pathway for degradation of MPs and it sheds light on an unusual MPs disposal mechanisms in nature. Abstract : The exceptionally rapid degradation of microplastics (MPs) in frozen solution was discovered. The activity is ascribed to selective generation of singlet oxygen in the narrow space of the liquid layer between ice crystals. The findings offer a highly efficient degradation pathway for MPs and shed light on mechanisms of disposal of MPs in nature.